Performance of the jet transport airplane : analysis methods, flight operations, and regulations - Young, Trevor M. (John Wiley & Sons, 2018)
Presenting a detailed and comprehensive treatment of performance analysis techniques for jet transport airplanes, this unique book describes key operational and regulatory procedures and constraints that directly impact the performance of commercial airliners. -- Edited summary from book.
Keywords: Jet transports -- Piloting.; Airplanes -- Performance.; Aeronautics, Commercial.; elektronické knihy; electronic books